Research on the Structure and Development of the Universe of Subjects - Neelameghan, A. (Journal of Information and Knowledge, 2002)
The study of the structure and development of the universe of subjects by the librarian is shown to be a necessary implication of the Five Laws of Library Science. The particular implications of each of the Laws are dealt with. Among the attributes of the universe of subjects to be studied are: Its tendency to become infinite and a continuum; its multidimensional and turbulently dynamic qualities; the emergence and modes of formation of subjects; the frequency and trend of incidence of each of the different modes; the strength of bond among the constituents of a subject; the frequency anll pattern of incidence of different kinds of facets; the impact of different kinds of ideas-intuition-based seminal and intellect-based near seminal ones; the use of subjects for different purposes and the rate of such utilisation, at differest periods over the last two hundred years; and the effect of the faults of the verbal plane on the idea plane. Other subjects in which the universe of subjects as a whole may be the subject of study from different angles, a syllabus for the subject, and some problems for pursuit, are mentioned.